Modification of UTAUT2 in assessing the use of E-Money in Surakarta - Fuad Hasyim (Jurnal Ekonomi Islam, 2022)
The globalization era has changed everything, including changing the order of the payment system in Indonesia. Currently e-money is growing rapidly in Indonesia, but it is not followed by the development of e-money users. E-money users in Indonesia are still considered low, this is because there are still many people who use cash. This study aims to measure people's interest in using e-money with the UTAUT 2 approach. The method used in this study is regression with the population of the Surakarta community with a sample of 102 respondents. The results showed that business expectations, hedonic motivation, price values and habits affect the interest in using e-money. Meanwhile, performance expectations, social factors and facilitating conditions have no effect on the interest in using e-money.